LEGAL REGULATION OF ENERGY SECURITY: THE UZBEK MODEL AND INTERNATIONAL EXPERIENCE - Valijanov, Dilmurod (Oriental Journal of History, Politics and Law, 2025)
The article analyzes the theoretical and legal aspects of the mechanisms for regulating energy security. The novelty of the research lies in the comprehensive analysis of legal mechanisms for ensuring energy security, state and prosecutorial supervision, as well as criminal law instruments. Based on comparative legal analysis, proposals and recommendations for improving the legislation of the Republic of Uzbekistan have been developed. The conclusion presents conceptual approaches to enhancing the legal foundations of energy security.